2021
DOI: 10.1186/s13054-021-03491-y
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus statements for the management of COVID-19-related acute respiratory failure using a Delphi method

Abstract: Background Coronavirus disease 2019 (COVID-19) pandemic has caused unprecedented pressure on healthcare system globally. Lack of high-quality evidence on the respiratory management of COVID-19-related acute respiratory failure (C-ARF) has resulted in wide variation in clinical practice. Methods Using a Delphi process, an international panel of 39 experts developed clinical practice statements on the respiratory management of C-ARF in areas where ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(143 citation statements)
references
References 72 publications
2
127
0
6
Order By: Relevance
“…Non-invasive respiratory support strategies may fail due to a variety of reasons, including P-SILI itself, high work of breathing, inadequate sedation, decreased level of consciousness, deterioration of gas exchange, interface intolerance, or underlying conditions. 63 A recent consensus of 39 experts 64 concerning the management of COVID-19-related acute respiratory failure using a Delphi method suggested that high-flow nasal oxygen therapy (HFNOT) should be used in patients who are unable to maintain peripheral oxygen saturation (SpO 2 ) > 90% despite oxygen delivery through a Venturi mask, to avoid the need for tracheal intubation and invasive mechanical ventilation. NPPV (with positive end-expiratory pressure, PEEP) should be considered when the patient’s work of breathing increases progressively or in case of mixed (hypoxic and hypercapnic) respiratory failure.…”
Section: How Can P-sili Be Prevented?mentioning
confidence: 99%
“…Non-invasive respiratory support strategies may fail due to a variety of reasons, including P-SILI itself, high work of breathing, inadequate sedation, decreased level of consciousness, deterioration of gas exchange, interface intolerance, or underlying conditions. 63 A recent consensus of 39 experts 64 concerning the management of COVID-19-related acute respiratory failure using a Delphi method suggested that high-flow nasal oxygen therapy (HFNOT) should be used in patients who are unable to maintain peripheral oxygen saturation (SpO 2 ) > 90% despite oxygen delivery through a Venturi mask, to avoid the need for tracheal intubation and invasive mechanical ventilation. NPPV (with positive end-expiratory pressure, PEEP) should be considered when the patient’s work of breathing increases progressively or in case of mixed (hypoxic and hypercapnic) respiratory failure.…”
Section: How Can P-sili Be Prevented?mentioning
confidence: 99%
“…Indeed, by promoting lung recruitment, prone position reduces hypoxemia, hypercapnia, driving pressure, and plateau pressure, thereby reducing the pulmonary vascular hydraulic load and improving RV function [145]. Most recent guidelines have endorsed prone positioning in the clinical management of severely hypoxemic COVID-19 patients, both under spontaneous awake ventilation (self-proning) and mechanical ventilation [147].…”
Section: Afterload Reductionmentioning
confidence: 99%
“…However, there is insufficient evidence for recommending a specific timing for tracheostomy. 48,49 We recommend leaving the decision on the relative merits of open versus percutaneous tracheostomy to the physician's discretion and institutional experience. 50 -Intubation and tracheostomy should be performed by the most experienced physician to minimize delay or related complications.…”
Section: Imentioning
confidence: 99%